2015
DOI: 10.1089/aid.2014.0060
|View full text |Cite
|
Sign up to set email alerts
|

Rate and Determinants of Residual Viremia in Multidrug-Experienced Patients Successfully Treated with Raltegravir-Based Regimens

Abstract: Residual HIV viremia, defined by low levels of plasma HIV RNA with enhanced-sensitivity assays, may persist even in the presence of successful antiretroviral therapy, but little is known about its determinants. Our objective was to evaluate the rate and determinants of residual viremia in patients who show stable undetectable plasma HIV-1 RNA with conventional assays. Forty-four multidrug-experienced patients with undetectable levels of HIV RNA for at least 2 years under raltegravir-based regimens were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Because residual HIV in individuals on effective suppressive ART shows only limited genetic diversification over-time, with no new appearance of ART resistance mutations (Bailey et al , 2006; Wong et al , 1997), it is unlikely that this virus arises from active virus replication in an unidentified tissue. In some studies, however, residual viremia can be reduced (but not eliminated) upon intensification of treatment (Baroncelli et al , 2015). Together these considerations suggest that other persistently-infected cells, in addition to memory T cells, contribute to stable residual viremia and chronic inflammatory diseases in patients on effective ART.…”
mentioning
confidence: 99%
“…Because residual HIV in individuals on effective suppressive ART shows only limited genetic diversification over-time, with no new appearance of ART resistance mutations (Bailey et al , 2006; Wong et al , 1997), it is unlikely that this virus arises from active virus replication in an unidentified tissue. In some studies, however, residual viremia can be reduced (but not eliminated) upon intensification of treatment (Baroncelli et al , 2015). Together these considerations suggest that other persistently-infected cells, in addition to memory T cells, contribute to stable residual viremia and chronic inflammatory diseases in patients on effective ART.…”
mentioning
confidence: 99%
“…An ultrasensitive method based on a modified real time PCR assay (VERSANT® HIV‐1 RNA 1.0 kPCR, Siemens Healthcare Diagnostics, Berkeley, CA), was used. The modified method had a detection limit of 2.5 HIV‐1 RNA copies/ml [Baroncelli et al, ]. Analysis were performed after 12 and 24 months from the beginning of the RAL‐based regimen.…”
Section: Methodsmentioning
confidence: 99%
“…Despite their great efficiency to inhibit the integration step, INSTIs are unable to impair the late stages of the viral replication cycle, and thus they can’t prevent new infections. Clinical studies have not only shown that low-level viremia can persist in patients with undetectable plasma HIV RNA (Maldarelli et al, 2007) including patients treated with RAL-based regimens (Baroncelli et al, 2015), but also that RAL intensification is unable to suppress this persistent residual viremia and is associated with an increase in circular uDNA (Dinoso et al, 2009; Buzon et al, 2010b; Gandhi et al, 2010; McMahon et al, 2010; Hatano et al, 2011; Vallejo et al, 2012). An evolution of HIV-1 envelope sequences despite potent antiviral therapy has previously been shown (Gunthard et al, 1999; Martinez et al, 1999) with the emergence of a NRTI resistance mutation (Martinez et al, 1999).…”
Section: Different Ways To Bypass Instis Effectsmentioning
confidence: 99%